Crystal structure of N-[(1Z)-1-(3-methyl-3-phenylcyclobutyl)-2- thiomorpholin-4-ylethylidene] thiourea - Sari, U.; Yilmaz, I.; Çukurovali, A.; Güven, K.; Aksoy, I. (My University, 2005)
The crystal structure of N-[(1Z)-1-(3-methyl-3-phenylcyclobutyl)-2- thiomorpholin-4-ylethylidene] thiourea (C18H26N 4S2) has been determined by X-ray crystallographic techniques. The compound crystallizes in the orthorhombic space group Pbca, with unit cell parameters: a = 15.692(3), b = 20.803(8), c = 11.979(6)Å, Z = 8, V = 3911(7)Å3. The crystal structure was solved by direct methods and refined by full-matrix least squares to a final R-value of 0.084 for 1447 observed reflections [I > 2?(I)]. In the thiosemicarbazide moiety, the S = C bond length is 1.656(6), N-C-N angle is 115.6(5)°. The crystal structure is stabilized by the intermolecular N-H...S hydrogen bonds. © 2005 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Biological activity; Crystal structure; Thiosemicarbazone; X-ray crystallography